Rancang Ulang dan Uji Kegunaan SPADA UNPRI: Menerapkan Nielsen’s Poisson Model - Hutauruk, Jesika Avonia; Indra, Evta (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2024)
This research aims to redesign and evaluate the usability of the SPADA website at Universitas Prima Indonesia (UNPRI) by applying Nielsen’s Poisson Model in usability testing. The primary objective is to enhance the website's interface for both new and returning users while reducing the number of respondents needed for usability tests without compromising the validity of the results. The research involves several prototype development iterations, each tested by different respondent groups. Results indicate significant improvements in user satisfaction and a reduction in task completion time with each iteration. Nielsen’s Poisson Model was effective in identifying usability issues, with major problems resolved in early iterations and minor ones discovered in later phases. The final prototype is expected to significantly improve the usability of the SPADA UNPRI website.